Medieval Latin Aristotle Commentaries Authors A-F - Lohr, Charles H. (Traditio, 1967)
The history of Latin Aristotelianism reaches roughly from Boethius to Galileo — from the end of classical civilization to the scientific revolution of the seventeenth century. Whereas the early Middle Ages knew only a part of Aristotle's logic, the whole Aristotelian corpus became known in the period around 1200. From the middle of the thirteenth century to the end of the Middle Ages, and in some circles even beyond, the influence of these works was decisive both for the system of education and for the development of philosophy and natural science.